Fe-Gd-B-Cu nanocrystalline alloy with excellent soft magnetic performance and preparation method and application of Fe-Gd-B-Cu nanocrystalline alloy

By introducing Cu into Fe-Gd-B nanocrystalline alloys and optimizing the element ratio, Fe-Gd-B-Cu nanocrystalline alloys were prepared using arc melting and high-vacuum single-roll quenching techniques. This solved the balance problem between coercivity and saturation magnetization in existing soft magnetic alloy materials, and achieved excellent performance of high-frequency transformer and motor stator/rotor core materials.

CN121506668APending Publication Date: 2026-02-10ELECTRIC POWER RES INST OF GUANGDONG POWER GRID CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511627403.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-07
Publication Date
2026-02-10

AI Technical Summary

Technical Problem

Existing soft magnetic alloy materials cannot achieve the best balance between coercivity and saturation magnetization, and therefore cannot meet the requirements of high-frequency transformer and motor stator/rotor core materials.

Method used

By introducing Cu into Fe-Gd-B nanocrystalline alloys and optimizing the element ratio, Fe-Gd-B-Cu nanocrystalline alloys were prepared using arc melting and high-vacuum single-roll quenching technology. The specific steps included arc melting and cooling and forming on copper rolls.

Benefits of technology

A nanocrystalline alloy with low coercivity and high saturation magnetization was obtained, which is suitable for magnetic devices with complex shapes and has excellent soft magnetic properties, making it suitable for magnetic materials such as transformers and sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121506668A_ABST
    Figure CN121506668A_ABST
Patent Text Reader

Abstract

The invention relates to a Fe-Gd-B-Cu nanocrystalline alloy with excellent soft magnetic performance and a preparation method and application of the Fe-Gd-B-Cu nanocrystalline alloy, and belongs to the technical field of alloy materials. The invention provides Fe-Gd-B-Cu with excellent soft magnetic performance, the atomic percentage expression of the nanocrystalline alloy is FexGdyBmCin, x is the atomic content corresponding to the Fe element, y is the atomic content corresponding to the Gd element, m is the atomic content corresponding to the B element, n is the atomic content corresponding to the Cu element, 85 < = x < = 95, 1 < = y < = 3, 5 < = m < = 8, 0.1 < = n < = 2, and x + y + m + n = 100. The Cu element is added into a Fe-Gd-B nanocrystalline alloy system, the soft magnetic performance of the nanocrystalline alloy material is optimized, the Fe-based alloy with excellent soft magnetic performance is obtained, typical soft magnetic performance is presented, and the nanocrystalline alloy with low coercive force and high saturation magnetization intensity is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of alloy materials technology, and in particular to a Fe-Gd-B-Cu nanocrystalline alloy with excellent soft magnetic properties, its preparation method, and its applications. Background Technology

[0002] Soft magnetic materials have found wide application in modern society. Pure iron, silicon steel, iron-silicon-aluminum alloys, iron-cobalt alloys, permalloy, ferrites, amorphous alloys, and nanocrystalline alloys can all be used as soft magnetic materials in appropriate application environments. Soft magnetic alloys are a class of alloys that exhibit high permeability and low coercivity in weak magnetic fields. Among them, iron-based nanocrystalline soft magnetic alloys typically possess high saturation magnetic flux density (Bs) and permeability (μ), as well as low high-frequency core loss (W) and near-zero magnetostriction, and have been widely used in the core materials of high-frequency transformers, switch-mode power supplies, and motor stators / rotors.

[0003] The main factors affecting the properties of soft magnetic alloys include the elemental composition, impurities, and grain orientation. Soft magnetic alloys with different elemental compositions possess different magnetic properties. For example, adding appropriate alloying elements, such as molybdenum, to iron-nickel alloys with a nickel content of 30%–90%, and employing suitable processes, can increase resistivity, reduce stress sensitivity, and simultaneously increase initial permeability, but the saturation magnetization and Curie point will decrease. In iron-silicon-aluminum alloys, the magnetic properties are more closely related to the composition; even slight deviations in composition can lead to a sharp decrease in magnetic properties. In iron-cobalt alloys, as the cobalt content increases, the saturation magnetic induction increases, and the Curie point also rises accordingly; at a cobalt content of 35%, Bs can reach over 2.4T.

[0004] Chinese patent CN103258633A discloses a method for preparing R-Fe-B sintered magnets. A layer of metallic Tb or Dy is coated onto the surface of a NdFeB sintered magnet using a thermal spraying method. Then, through heat treatment, the Tb or Dy sprayed onto the magnet surface diffuses into the interior of the sintered magnet through grain boundaries at high temperatures, significantly improving the coercivity of the sintered magnet. However, the material prepared using this method has a low Fe content and high coercivity, making it unsuitable for manufacturing materials such as transformer cores.

[0005] In the practical development and application of soft magnetic materials, the types and contents of each element are never isolated variables. They are the starting point for material design, and through synergistic effects with other elements, the magnetic, electrical, and mechanical properties of the material can ultimately be "tailored" to meet the needs of specific application scenarios. Therefore, it is necessary to develop new elemental compositions and preparation methods for soft magnetic materials to comprehensively control their soft magnetic properties and adapt them to their application scenarios. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a Fe-Gd-B-Cu nanocrystalline alloy with excellent soft magnetic properties, its preparation method and application.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides an Fe-Gd-B-Cu nanocrystalline alloy with excellent soft magnetic properties, wherein the atomic percentage expression of the nanocrystalline alloy is Fe x Gd y B m Cu n Where x is the atomic content of Fe, y is the atomic content of Gd, m is the atomic content of B, n is the atomic content of Cu, 85≤x≤95, 1≤y≤3, 5≤m≤8, 0.1≤n≤2, and x+y+m+n=100.

[0008] This invention obtains a Fe-Gd-B-Cu nanocrystalline alloy with excellent soft magnetic properties by adding Cu to the Fe-Gd-B alloy system.

[0009] In a preferred embodiment of the Fe-Gd-B-Cu nanocrystalline alloy of the present invention, 89.2 ≤ x ≤ 90.7.

[0010] In a preferred embodiment of the Fe-Gd-B-Cu nanocrystalline alloy of the present invention, 2.3≤y≤2.35.

[0011] In a preferred embodiment of the Fe-Gd-B-Cu nanocrystalline alloy of the present invention, 6.9 ≤ m ≤ 7.

[0012] In a preferred embodiment of the Fe-Gd-B-Cu nanocrystalline alloy of the present invention, 0.25≤n≤1.5.

[0013] In a preferred embodiment of the Fe-Gd-B-Cu nanocrystalline alloy of the present invention, x = 90.7-n.

[0014] In a more preferred embodiment of the Fe-Gd-B-Cu nanocrystalline alloy of the present invention, y = 2.32 and x = 6.98.

[0015] In a preferred embodiment of the Fe-Gd-B-Cu nanocrystalline alloy of the present invention, the thickness of the Fe-Gd-B-Cu nanocrystalline alloy is 18-22 μm.

[0016] As a more preferred embodiment of the Fe-Gd-B-Cu nanocrystalline alloy of the present invention, the thickness of the Fe-Gd-B-Cu nanocrystalline alloy is 20 μm.

[0017] As a more preferred embodiment of the Fe-Gd-B-Cu nanocrystalline alloy of the present invention, the atomic percentage expression of the Fe-Gd-B-Cu nanocrystalline alloy is: Fe 90.20 Gd 2.32 B 6.98 Cu 0.50 It has lower coercivity (9.38 A / m) and higher saturation magnetization (1.69 T), exhibiting superior soft magnetic properties.

[0018] As a more preferred embodiment of the Fe-Gd-B-Cu nanocrystalline alloy of the present invention, the atomic percentage expression of the Fe-Gd-B-Cu nanocrystalline alloy is: Fe 89.95 Gd 2.32 B 6.98 Cu 0.75 It has lower coercivity (7.11 A / m) and higher saturation magnetization (1.74 T), exhibiting superior soft magnetic properties.

[0019] As a more preferred embodiment of the Fe-Gd-B-Cu nanocrystalline alloy of the present invention, the atomic percentage expression of the Fe-Gd-B-Cu nanocrystalline alloy is: Fe 89.70 Gd 2.32 B 6.98 Cu 1.00 It has lower coercivity (10.46 A / m) and higher saturation magnetization (1.68 T), exhibiting superior soft magnetic properties.

[0020] Secondly, the present invention provides a method for preparing the Fe-Gd-B-Cu nanocrystalline alloy, comprising the following steps: S1, the elemental raw materials of the Fe-Gd-B-Cu nanocrystalline alloy are subjected to arc melting under inert gas conditions according to the stoichiometric ratio to form an alloy ingot; S2. The alloy ingot from step S1 is placed in a high-vacuum single-roller quenching system. Under inert gas conditions, the alloy ingot from step S1 is melted into alloy droplets and dripped onto a copper roller. After cooling and forming, the Fe-Gd-B-Cu nanocrystalline alloy is obtained.

[0021] As a preferred embodiment of the preparation method described in this invention, in step S1, each elemental raw material is ultrasonically cleaned in petroleum ether and anhydrous ethanol in sequence before use.

[0022] In a preferred embodiment of the preparation method described in this invention, in step S1, the elemental raw materials are placed in the order of lower melting point at the bottom and higher melting point at the top.

[0023] In a preferred embodiment of the preparation method described in this invention, the melting current in step S1 is 200–500 A.

[0024] In a more preferred embodiment of the preparation method described in this invention, the melting current in step S1 is 450A.

[0025] In a preferred embodiment of the preparation method of the present invention, in step S1 or S2, the inert gas is selected from at least one of argon, nitrogen and helium.

[0026] In a preferred embodiment of the preparation method described in this invention, the inert gas in step S1 is argon.

[0027] In a preferred embodiment of the preparation method described in this invention, in step S1 or S2, the purity of the inert gas introduced is 99.95 to 99.99 wt%.

[0028] As a more preferred embodiment of the preparation method of the present invention, in step S1 or S2, the purity of the inert gas introduced is 99.99 wt%.

[0029] In a preferred embodiment of the preparation method described in this invention, in step S1 or S2, a vacuum is drawn to a pressure of 3.5 × 10⁻⁶. -3 ~5×10 -3 When Pa, inert gas is introduced again.

[0030] In a more preferred embodiment of the preparation method described in this invention, in step S1 or S2, a vacuum is drawn to a pressure of 3.5 × 10⁻⁶. -3 When Pa, inert gas is introduced again.

[0031] In a preferred embodiment of the preparation method described in this invention, in step S1, arc melting is carried out under a gas pressure of -0.08 to 0.03 MPa.

[0032] As a more preferred embodiment of the preparation method of the present invention, in step S1, arc melting is carried out at a gas pressure of -0.08 MPa.

[0033] In a preferred embodiment of the preparation method described in this invention, in step S1, the raw materials are melted until all the elemental materials are melted to form an alloy ingot, cooled, the alloy ingot is flipped, melted again, and magnetically stirred.

[0034] In a preferred embodiment of the preparation method described in this invention, in step S1, the electric arc melting is repeated 5 to 10 times.

[0035] As a more preferred embodiment of the preparation method described in this invention, in step S1, the electric arc melting is repeated 6 times.

[0036] In a preferred embodiment of the preparation method described in this invention, in step S2, the alloy ingot from step S1 is melted into alloy droplets under a gas pressure of 350–400 mbar.

[0037] In a preferred embodiment of the preparation method described in this invention, in step S2, the alloy ingot from step S1 is melted into alloy droplets under a pressure of 400 mbar.

[0038] In a preferred embodiment of the preparation method described in this invention, in step S2, the alloy ingot is first melted under a current of 200-300A, and then completely melted under a current of 400-500A.

[0039] As a more preferred embodiment of the preparation method described in this invention, in step S2, the alloy ingot is first melted under a current of 300A, and then completely melted under a current of 450A.

[0040] In a preferred embodiment of the preparation method described in this invention, in step S2, the rotational speed of the copper roller is 3200–3400 r / min.

[0041] In a preferred embodiment of the preparation method described in this invention, the rotational speed of the copper roller in step S2 is 3300 r / min.

[0042] Thirdly, the present invention provides the application of the Fe-Gd-B-Cu nanocrystalline alloy in the preparation of magnetic materials, such as transformers and sensors.

[0043] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention optimizes the soft magnetic properties of Fe-Gd-B nanocrystalline alloys by adding Cu to the Fe-Gd-B nanocrystalline alloy system, thereby obtaining Fe-based alloys with excellent soft magnetization performance. The magnetization intensity increases sharply with the increase of magnetic field under low magnetic field and then gradually reaches saturation, indicating that this alloy system exhibits typical soft magnetic properties. It is capable of fabricating magnetic devices with complex shapes. The fabrication method is simple and easy to implement, and it has broad application prospects in the field of magnetic materials.

[0044] 2. This invention explores the relationship between the contents of each element in Fe-Gd-B-Cu nanocrystalline alloys, and determines the optimal contents of each element when preparing Fe-Gd-B-Cu nanocrystalline alloys with excellent soft magnetization properties. Nanocrystalline alloys with low coercivity and high saturation magnetization can be prepared, with coercivity reaching 7.11 A / m and saturation magnetization reaching 1.74 T. Attached Figure Description

[0045] Figure 1 X-ray diffraction images of the nanocrystalline alloys prepared in Examples 1-3 and Comparative Examples 2-4 of this invention; Figure 2 The saturation magnetization curves are shown for the nanocrystalline alloys prepared in Examples 1-3 and Comparative Examples 2-4 of this invention. Figure 3 The saturation magnetization curves are for the nanocrystalline alloys prepared in Comparative Examples 1 and 5 of this invention. Detailed Implementation

[0046] To better illustrate the purpose, technical solution, and advantages of this invention, the invention will be further described below with reference to specific embodiments. Unless otherwise specified, other materials and reagents used in the embodiments are commercially available.

[0047] Example 1 This embodiment provides a Fe-Gd-B-Cu nanocrystalline alloy with excellent soft magnetic properties, the atomic percentage expression of which is Fe 90.20 Gd 2.32 B 6.98 Cu 0.50 The thickness is 20 μm, and the preparation method is as follows: 1. Using elemental Fe, Gd, B, and Cu with a purity of not less than 99.9% as raw materials, according to the atomic percentage expression of nanocrystalline alloys, Fe... 90.20 Gd 2.32 B 6.98 Cu 0.50 The sample was weighed according to the elemental ratio (atomic ratio) to obtain the elemental raw materials, of which Fe 91.43 g, Gd 6.62 g, B 1.37 g, and Cu 0.58 g. Before use, each elemental raw material was ultrasonically cleaned sequentially in petroleum ether and anhydrous ethanol to obtain the cleaned elemental raw materials.

[0048] 2. Place the elemental raw materials cleaned in step 1 into a copper crucible, in the following order: lower melting point at the bottom, higher melting point at the top. Evacuate the crucible to a vacuum level of 3.5 × 10⁻⁶. -3 Pa, then high-purity argon gas with a purity of 99.99 wt% is introduced as a protective gas until the pressure inside the furnace reaches -0.08 MPa. Then, the gas supply is stopped, and electric arc melting is carried out with a melting current of 450 A. The entire mixture is melted to form an alloy ingot. After cooling, the alloy ingot is flipped over and melted again with magnetic stirring. This melting process is repeated 6 times to obtain an alloy ingot.

[0049] 3. Place the alloy ingot prepared in step 2 into the quartz tube of a high-vacuum single-roller quenching system. After evacuation, introduce high-purity argon gas (99.99 wt%) to a pressure of 400 mbar. First, melt the alloy ingot under a low current (300 A), then completely melt it under a high current (450 A) to obtain alloy droplets. Drop the alloy droplets onto a rapidly rotating (3300 r / min) copper roller and cool to form the alloy, thus obtaining the alloy with the atomic percentage expression Fe. 90.20 Gd 2.32 B 6.98 Cu 0.50 Fe-Gd-B-Cu nanocrystalline alloy.

[0050] Example 2 This embodiment provides a Fe-Gd-B-Cu nanocrystalline alloy with excellent soft magnetic properties, the atomic percentage expression of which is Fe 89.95 Gd 2.32 B 6.98 Cu 0.75 The thickness is 20 μm, and the preparation method is as follows: 1. Using elemental Fe, Gd, B, and Cu with a purity of not less than 99.9% as raw materials, according to the atomic percentage expression of nanocrystalline alloys, Fe... 89.95 Gd 2.32 B 6.98 Cu 0.75 The sample was weighed according to the elemental ratio (atomic ratio) to obtain the elemental raw materials, of which Fe 91.95g, Gd 6.62g, B 1.37g, and Cu 0.86g. Before use, each elemental raw material was ultrasonically cleaned sequentially in petroleum ether and anhydrous ethanol to obtain the cleaned elemental raw materials.

[0051] 2. Place the elemental raw materials cleaned in step 1 into a copper crucible, in the following order: lower melting point at the bottom, higher melting point at the top. Evacuate the crucible to a vacuum level of 3.5 × 10⁻⁶. -3 Pa, then high-purity argon gas with a purity of 99.99 wt% is introduced as a protective gas until the pressure inside the furnace reaches -0.08 MPa. Then, the gas supply is stopped, and electric arc melting is carried out at a melting current of 450 A. The entire mixture is melted to form an alloy ingot. After cooling, the alloy ingot is flipped over and melted again with magnetic stirring. This melting process is repeated 6 times to obtain an alloy ingot.

[0052] 3. Place the alloy ingot prepared in step 2 into the quartz tube of a high-vacuum single-roller quenching system. After evacuation, introduce high-purity argon gas (99.99 wt%) to a pressure of 400 mbar. First, melt the alloy ingot under a low current (300 A), then completely melt it under a high current (450 A) to obtain alloy droplets. Drop the alloy droplets onto a rapidly rotating (3300 r / min) copper roller and cool to form the alloy, thus obtaining the alloy with the atomic percentage expression Fe.89.95 Gd 2.32 B 6.98 Cu 0.75 Fe-Gd-B-Cu nanocrystalline alloy.

[0053] Example 3 This embodiment provides a Fe-Gd-B-Cu nanocrystalline alloy with excellent soft magnetic properties, the atomic percentage expression of which is Fe 89.70 Gd 2.32 B 6.98 Cu 1.00 The thickness is 20 μm, and the preparation method is as follows: 1. Using elemental Fe, Gd, B, and Cu with a purity of not less than 99.9% as raw materials, according to the atomic percentage expression of nanocrystalline alloys, Fe... 89.70 Gd 2.32 B 6.98 Cu 1.00 The elements were weighed according to their atomic ratios to obtain the raw materials of each element: Fe 90.86 g, Gd 6.62 g, B 1.37 g, and Cu 1.15 g. Before use, each elemental raw material was ultrasonically cleaned sequentially in petroleum ether and anhydrous ethanol to obtain the cleaned raw materials of each element.

[0054] 2. Place the elemental raw materials cleaned in step 1 into a copper crucible, in the following order: lower melting point at the bottom, higher melting point at the top. Evacuate the crucible to a vacuum level of 3.5 × 10⁻⁶. -3 Pa, then high-purity argon gas with a purity of 99.99 wt% is introduced as a protective gas until the pressure inside the furnace reaches -0.08 MPa. Then, the gas supply is stopped, and electric arc melting is carried out at a melting current of 450 A. The entire mixture is melted to form an alloy ingot. After cooling, the alloy ingot is flipped over and melted again with magnetic stirring. This melting process is repeated 6 times to obtain an alloy ingot.

[0055] 3. Place the alloy ingot prepared in step 2 into the quartz tube of a high-vacuum single-roller quenching system. After evacuation, introduce high-purity argon gas (99.99 wt%) to a pressure of 400 mbar. First, melt the alloy ingot under a low current (300 A), then completely melt it under a high current (450 A) to obtain alloy droplets. Drop the alloy droplets onto a rapidly rotating (3300 r / min) copper roller and cool to form the alloy, thus obtaining the alloy with the atomic percentage expression Fe. 89.70 Gd 2.32 B 6.98 Cu 1.00 Fe-Gd-B-Cu nanocrystalline alloy.

[0056] Comparative Example 1 This embodiment provides an Fe-Gd-B nanocrystalline alloy, whose atomic percentage expression is Fe90.70 Gd 2.32 B 6.98 The thickness is 20 μm, and the preparation method is as follows: 1. Using Fe, Gd, and B elements with a purity of not less than 99.9% as raw materials, according to the atomic percentage expression of nanocrystalline alloys, Fe... 90.70 Gd 2.32 B 6.98 The elements were weighed according to their atomic ratios to obtain the raw materials of each element, including 92 g of Fe, 6.63 g of Gd, and 1.37 g of B. Before use, each elemental raw material was ultrasonically cleaned sequentially in petroleum ether and anhydrous ethanol to obtain the cleaned raw materials of each element.

[0057] 2. Place the elemental raw materials cleaned in step 1 into a copper crucible, in the following order: lower melting point at the bottom, higher melting point at the top. Evacuate the crucible to a vacuum level of 3.5 × 10⁻⁶. -3 Pa, then high-purity argon gas with a purity of 99.99 wt% is introduced as a protective gas until the pressure inside the furnace reaches -0.08 MPa. Then, the gas supply is stopped, and electric arc melting is carried out at a melting current of 450 A. The entire mixture is melted to form an alloy ingot. After cooling, the alloy ingot is flipped over and melted again with magnetic stirring. This melting process is repeated 6 times to obtain an alloy ingot.

[0058] 3. Place the alloy ingot prepared in step 2 into the quartz tube of a high-vacuum single-roller quenching system. After evacuation, introduce high-purity argon gas (99.99 wt%) to a pressure of 400 mbar. First, melt the alloy ingot under a low current (300 A), then completely melt it under a high current (450 A) to obtain alloy droplets. Drop the alloy droplets onto a rapidly rotating (3300 r / min) copper roller and cool to form the alloy, thus obtaining the alloy with the atomic percentage expression Fe. 90.70 Gd 2.32 B 6.98 Fe-Gd-B nanocrystalline alloy.

[0059] Comparative Example 2 This embodiment provides an Fe-Gd-B-Cu nanocrystalline alloy, whose atomic percentage expression is Fe 90.45 Gd 2.32 B 6.98 Cu 0.25 The thickness is 20 μm, and the preparation method is as follows: 1. Using elemental Fe, Gd, B, and Cu with a purity of not less than 99.9% as raw materials, according to the atomic percentage expression of nanocrystalline alloys, Fe... 90.45 Gd 2.32 B 6.98 Cu 0.25The elements were weighed according to their atomic ratios to obtain the raw materials of each element: Fe 91.72 g, Gd 6.62 g, B 1.37 g, and Cu 0.29 g. Before use, each elemental raw material was ultrasonically cleaned sequentially in petroleum ether and anhydrous ethanol to obtain the cleaned raw materials of each element.

[0060] 2. Place the elemental raw materials cleaned in step 1 into a copper crucible, in the following order: lower melting point at the bottom, higher melting point at the top. Evacuate the crucible to a vacuum level of 3.5 × 10⁻⁶. -3 Pa, then high-purity argon gas with a purity of 99.99 wt% is introduced as a protective gas until the pressure inside the furnace reaches -0.08 MPa. Then, the gas supply is stopped, and electric arc melting is carried out at a melting current of 450 A. The entire mixture is melted to form an alloy ingot. After cooling, the alloy ingot is flipped over and melted again with magnetic stirring. This melting process is repeated 6 times to obtain an alloy ingot.

[0061] 3. Place the alloy ingot prepared in step 2 into the quartz tube of a high-vacuum single-roller quenching system. After evacuation, introduce high-purity argon gas (99.99 wt%) to a pressure of 400 mbar. First, melt the alloy ingot under a low current (300 A), then completely melt it under a high current (450 A) to obtain alloy droplets. Drop the alloy droplets onto a rapidly rotating (3300 r / min) copper roller and cool to form the alloy, thus obtaining the alloy with the atomic percentage expression Fe. 90.45 Gd 2.32 B 6.98 Cu 0.25 Fe-Gd-B-Cu nanocrystalline alloy.

[0062] Comparative Example 3 This embodiment provides an Fe-Gd-B-Cu nanocrystalline alloy, whose atomic percentage expression is Fe 89.45 Gd 2.32 B 6.98 Cu 1.25 The thickness is 20 μm, and the preparation method is as follows: 1. Using elemental Fe, Gd, B, and Cu with a purity of not less than 99.9% as raw materials, according to the atomic percentage expression of nanocrystalline alloys, Fe... 89.45 Gd 2.32 B 6.98 Cu 1.25 The elements were weighed according to their atomic ratios to obtain the raw materials of each element: Fe 90.58 g, Gd 6.61 g, B 1.37 g, and Cu 1.44 g. Before use, each elemental raw material was ultrasonically cleaned sequentially in petroleum ether and anhydrous ethanol to obtain the cleaned raw materials of each element.

[0063] 2. Place the elemental raw materials cleaned in step 1 into a copper crucible, in the following order: lower melting point at the bottom, higher melting point at the top. Evacuate the crucible to a vacuum level of 3.5 × 10⁻⁶. -3 Pa, then high-purity argon gas with a purity of 99.99 wt% is introduced as a protective gas until the pressure inside the furnace reaches -0.08 MPa. Then, the gas supply is stopped, and electric arc melting is carried out at a melting current of 450 A. The entire mixture is melted to form an alloy ingot. After cooling, the alloy ingot is flipped over and melted again with magnetic stirring. This melting process is repeated 6 times to obtain an alloy ingot.

[0064] 3. Place the alloy ingot prepared in step 2 into the quartz tube of a high-vacuum single-roller quenching system. After evacuation, introduce high-purity argon gas (99.99 wt%) to a pressure of 400 mbar. First, melt the alloy ingot under a low current (300 A), then completely melt it under a high current (450 A) to obtain alloy droplets. Drop the alloy droplets onto a rapidly rotating (3300 r / min) copper roller and cool to form the alloy, thus obtaining the alloy with the atomic percentage expression Fe. 89.45 Gd 2.32 B 6.98 Cu 1.25 Fe-Gd-B-Cu nanocrystalline alloy.

[0065] Comparative Example 4 This embodiment provides an Fe-Gd-B-Cu nanocrystalline alloy, whose atomic percentage expression is Fe 89.20 Gd 2.32 B 6.98 Cu 1.50 The thickness is 20 μm, and the preparation method is as follows: 1. Using elemental Fe, Gd, B, and Cu with a purity of not less than 99.9% as raw materials, according to the atomic percentage expression of nanocrystalline alloys, Fe... 89.20 Gd 2.32 B 6.98 Cu 1.50 The elements were weighed according to their atomic ratios to obtain the raw materials of each element: Fe 90.29 g, Gd 6.61 g, B 1.37 g, and Cu 1.73 g. Before use, each elemental raw material was ultrasonically cleaned sequentially in petroleum ether and anhydrous ethanol to obtain the cleaned raw materials of each element.

[0066] 2. Place the elemental raw materials cleaned in step 1 into a copper crucible, in the following order: lower melting point at the bottom, higher melting point at the top. Evacuate the crucible to a vacuum level of 3.5 × 10⁻⁶. -3Pa, then high-purity argon gas with a purity of 99.99 wt% is introduced as a protective gas until the pressure inside the furnace reaches -0.08 MPa. Then, the gas supply is stopped, and electric arc melting is carried out at a melting current of 450 A. The entire mixture is melted to form an alloy ingot. After cooling, the alloy ingot is flipped over and melted again with magnetic stirring. This melting process is repeated 6 times to obtain an alloy ingot.

[0067] 3. Place the alloy ingot prepared in step 2 into the quartz tube of a high-vacuum single-roller quenching system. After evacuation, introduce high-purity argon gas (99.99 wt%) to a pressure of 400 mbar. First, melt the alloy ingot under a low current (300 A), then completely melt it under a high current (450 A) to obtain alloy droplets. Drop the alloy droplets onto a rapidly rotating (3300 r / min) copper roller and cool to form the alloy, thus obtaining the alloy with the atomic percentage expression Fe. 89.20 Gd 2.32 B 6.98 Cu 1.50 Fe-Gd-B-Cu nanocrystalline alloy.

[0068] Comparative Example 5 This embodiment provides a Fe-Gd-B-Al nanocrystalline alloy, whose atomic percentage expression is Fe 89.95 Gd 2.32 B 6.98 Al 0.75 The thickness is 20 μm, and the preparation method is as follows: 1. Using Fe, Gd, B, and Al elements with a purity of not less than 99.9% as raw materials, according to the atomic percentage expression of nanocrystalline alloys, Fe... 89.95 Gd 2.32 B 6.98 Al 0.75 The sample was weighed according to the elemental ratio (atomic ratio) to obtain the elemental raw materials, of which Fe 91.6 g, Gd 6.65 g, B 1.38 g, and Al 0.37 g. Before use, each elemental raw material was ultrasonically cleaned sequentially in petroleum ether and anhydrous ethanol to obtain the cleaned elemental raw materials.

[0069] 2. Place the elemental raw materials cleaned in step 1 into a copper crucible, in the following order: lower melting point at the bottom, higher melting point at the top. Evacuate the crucible to a vacuum level of 3.5 × 10⁻⁶. -3 Pa, then high-purity argon gas with a purity of 99.99 wt% is introduced as a protective gas until the pressure inside the furnace reaches -0.08 MPa. Then, the gas supply is stopped, and electric arc melting is carried out at a melting current of 450 A. The entire mixture is melted to form an alloy ingot. After cooling, the alloy ingot is flipped over and melted again with magnetic stirring. This melting process is repeated 6 times to obtain an alloy ingot.

[0070] 3. Place the alloy ingot prepared in step 2 into the quartz tube of a high-vacuum single-roller quenching system. After evacuation, introduce high-purity argon gas (99.99 wt%) to a pressure of 400 mbar. First, melt the alloy ingot under a low current (300 A), then completely melt it under a high current (450 A) to obtain alloy droplets. Drop the alloy droplets onto a rapidly rotating (3300 r / min) copper roller and cool to form the alloy, thus obtaining the alloy with the atomic percentage expression Fe. 89.95 Gd 2.32 B 6.98 Al 0.75 Fe-Gd-B-Al nanocrystalline alloy.

[0071] The coercivity and saturation magnetization of the nanocrystalline alloys prepared in Examples 1-3 and Comparative Examples 1-5 were tested using a vibrating sample magnetometer (VSM). The vibration of the sample in the coil induces an alternating signal in the detection coil. The alternating voltage is proportional to the magnetic moment of the sample. The measured hysteresis loop was analyzed and calculated to obtain the coercivity and saturation magnetization results. The test results are shown in Table 1.

[0072] Table 1 like Figure 1 The image shown is an X-ray diffraction image of the nanocrystalline alloys prepared in Examples 1-3 and Comparative Examples 2-4 of this invention.

[0073] As shown in Table 1, the saturation magnetization of the samples in Examples 1-3 of this application varied with the amount of Cu added. Compared with Comparative Example 1, the addition of Cu to the Fe-Gd-B nanocrystalline alloy significantly improved the soft magnetic properties of the final nanocrystalline alloy sample, reducing coercivity and significantly increasing saturation magnetization, thus enhancing the soft magnetic properties of the nanocrystalline alloy sample. If Cu was replaced with Al (Comparative Example 5), the coercivity of the nanocrystalline alloy sample increased, and the saturation magnetization decreased accordingly. If the amount of Cu added was too small (Comparative Example 2), the coercivity increased and the saturation magnetization decreased. If the amount of Cu added was too large (Comparative Examples 3 and 4), although the coercivity decreased to some extent, the saturation magnetization decreased, and it was still impossible to obtain a nanocrystalline alloy with excellent soft magnetic properties. Therefore, Examples 1-3 have superior soft magnetic properties compared to Comparative Examples 2-5.

[0074] like Figure 2 As shown, compared with Comparative Examples 2-4, the magnetization of the nanocrystalline alloys prepared in Examples 1-3 increases sharply with the increase of magnetic field under low magnetic field and then gradually reaches saturation, indicating that this alloy system exhibits typical soft magnetic properties.

[0075] like Figure 3As shown, the nanocrystalline alloys prepared in Comparative Examples 1 and 5 have low saturation magnetization.

[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A Fe-Gd-B-Cu nanocrystalline alloy with excellent soft magnetic properties, characterized in that, The atomic percentage expression for the nanocrystalline alloy is Fe x Gd y B m Cu n Where x is the atomic content of Fe, y is the atomic content of Gd, m is the atomic content of B, n is the atomic content of Cu, 85≤x≤95, 1≤y≤3, 5≤m≤8, 0.1≤n≤2, and x+y+m+n=100.

2. The Fe-Gd-B-Cu nanocrystalline alloy as described in claim 1, characterized in that, In the Fe-Gd-B-Cu nanocrystalline alloy, 89.2 ≤ x ≤ 90.

7.

3. The Fe-Gd-B-Cu nanocrystalline alloy as described in claim 1, characterized in that, In the Fe-Gd-B-Cu nanocrystalline alloy, 2.3 ≤ y ≤ 2.

35.

4. The Fe-Gd-B-Cu nanocrystalline alloy as described in claim 1, characterized in that, In the Fe-Gd-B-Cu nanocrystalline alloy, 6.9 ≤ m ≤ 7.

5. The Fe-Gd-B-Cu nanocrystalline alloy as described in claim 1, characterized in that, In the Fe-Gd-B-Cu nanocrystalline alloy, 0.25≤n≤1.

5.

6. The Fe-Gd-B-Cu nanocrystalline alloy as described in claim 1, characterized in that, In the Fe-Gd-B-Cu nanocrystalline alloy, x = 90.7-n.

7. The Fe-Gd-B-Cu nanocrystalline alloy as described in claim 6, characterized in that, y = 2.32, x = 6.

98.

8. The method for preparing the Fe-Gd-B-Cu nanocrystalline alloy according to any one of claims 1 to 7, characterized in that, Includes the following steps: S1. The elemental raw materials in the Fe-Gd-B-Cu nanocrystalline alloy are melted by electric arc under inert gas conditions according to the stoichiometric ratio to form an alloy ingot. S2. The alloy ingot from step S1 is placed in a high-vacuum single-roller quenching system. Under inert gas conditions, the alloy ingot from step S1 is melted into alloy droplets and dripped onto a copper roller. After cooling and forming, the Fe-Gd-B-Cu nanocrystalline alloy is obtained.

9. The method for preparing the Fe-Gd-B-Cu nanocrystalline alloy as described in claim 8, characterized in that, In step S1, the smelting current is 200-500A.

10. The application of the Fe-Gd-B-Cu nanocrystalline alloy according to any one of claims 1 to 7 in the preparation of magnetic materials.

Citation Information

Patent Citations

  • Method for preparing R-Fe-B series sintered magnets

    CN103258633A